Propagación vegetativa de plátano dominique (musa paradisiaca) bajo dos porcentajes de sombra con la aplicación de cuatro dosis de benzilaminopurina (bap) en el cantón El Empalme provincia del Guayas - Meza Tuarez, José Eriberto (2013)
Lack of banana plantations that come from selected material for their phenotypic characteristics and resistance to pests and diseases, has affected in the different agronomic behavior of the specie. For this reason, it is necessary to have selection and propagation techniques to counteract this problem. Four doses were evaluated of benzylaminopurine (BAP) on vegetative propagation “Dominique” banana variety (Musa paradisiaca) under two shade percentages. The research was conducted in a greenhouse located in the Guayas parish of the El Emplame canton Guayas Province during the months March to May 2012. It was used a completely randomized design DBCA with factorial two (50% and 80% light intensity) by four (0 mg L-1, 40 mg L-1, 60 mg L-1, 80 mg L-1 BAP) giving eight treatments, four observations and each experimental unit consisted of six strains. To determine differences between measures was used to test Tukey (PC = 0.5). As evaluation criterion was used after 75 days the number, length and diameter of shoots, survival rate and force of outbreaks. T3 treatment (60 mg L-1 BAP positively influenced the issuance of outbreaks in Dominican banana, being induced by the greater number of total regrowth treatment….